Disaster Preparedness in the Emergency Department Using In Situ Simulation. (January 2016) - Jung, Deanna; Carman, Margaret; Aga, Ryan; Burnett, Aaron
Abstract : High influxes of patients during disasters have led to increased incidence of medical errors in emergency departments (EDs), ultimately leading to poor patient outcomes. Nearly 30% of errors committed in EDs are due to deficiencies in knowledge and skills, and between 60% and 70% of errors occur due in part from communication breakdowns. The goal of this project was to examine whether in situ simulation will increase health care providers' knowledge of how to perform during a disaster, improve competency in skills related to those actions, and to improve communication regarding the special circumstances inherent to a disaster in the ED. A mixed-methods pilot project analyzed the effects of in situ simulation. Results of the project demonstrate that in situ simulation can improve knowledge and communication during a disaster situation. Abstract : Supplemental Digital Content is Available in the Text.